Peptide charge state determination of tandem mass spectra from low-resolution collision induced dissociation - Shi, Jinhong (BioMed Central, 2011)
ABSTRACT: BACKGROUND: Charge states of tandem mass spectra from low-resolution collision induced dissociation can not be determined by mass spectrometry. As a result, such spectra with multiple charges are usually searched multiple times by assuming each possible charge state. Not only does this strategy increase the overall database search time, but also yields more false positives. Hence, it is advantageous to determine charge states of such spectra before database search. RESULTS: We propose a new approach capable of determining the charge states of low-resolution tandem mass spectra. Four novel and discriminant features are introduced to describe tandem mass spectra and used in Gaussian mixture model to distinguish doubly and triply charged peptides. By testing on three independent datasets with known validity, the results have shown that this method can assign charge states to low-resolution tandem mass spectra more accurately than existing methods. CONCLUSIONS: The proposed method can be used to improve the speed and reliability of peptide identification.